Survey on Knowledge, Attitude, Perception and Practice among University Students during the COVID-19 Pandemic - Md. Abdul Wadood; ASMA Mamun; Md. Abdur Rafi; Md. Kamrul Islam; Suhaili Mohd; Lai Lee Lee; Saw Aik; Md. Golam Hossain (Ital Publication, 2021)
Background: The numbers of infections and death by COVID-19 have continued to rise worldwide and preventive practice has remained to be one of the most effective ways to prevent it. We conducted this study to survey the knowledge, attitude, perception and practice of university students during the early stage of the pandemic in Bangladesh. Methods: This was a cross-sectional study with 305 students from Rajshahi University, conducted between March 11 and March 19, 2020. We developed a questionnaire for collecting information regarding COVID-19 following the instructions and guidelines of WHO and used frequency distribution, Kolmogorov-Smirnov test and Mann-Whitney and Kruskal-Wallis (non-parametric) tests for data analysis. Statistical significance was accepted at p < 0.05. Results: The knowledge of the students on COVID-19 was of average level; however, more than one-third of them were unwilling to avoid public transport and travel public places with friends and family. Their practice of preventive measures was not at a satisfactory level. More than one-third of them were not keen to stay home and not hesitant to visit crowded places. About half of the students thought the pandemic would not affect their daily activities, and most of them felt it would not affect their study, financial status, fieldwork of their course, or meeting with their friends and relatives. Female students were found more knowledgeable than male ones. Conclusions: The general knowledge of students had an average level on COVID-19, but their attitude, perception and preventive practices were not consistent with their level of education. The authorities should consider the findings while promulgating policies and implementing measures for the prevention of COVID-19.   Doi: 10.28991/SciMedJ-2021-03-SI-9 Full Text: PDF